Evaluation of the effect of finishing on the surface roughness of Paricá wood (Schizolobium amazonicum Huber ex Ducke) (Research, Society and Development, 2023)
Society's growing demand for wood products makes the search for knowledge about planted species increasingly indispensable, as they reduce the pressure exerted on native forests. In this way, the present work aimed to investigate characteristics of the roughness of Paricá wood (Schizolobium amazonicum), through the parameters Ra and Rz, after the pieces were subjected to the sanding process with sandpaper of different grain sizes, varying between 80 to 600 grains, to so allocate them to their best use. For this purpose, the drag roughness meter, model SURFTEST SJ-210, was used. The results obtained were analyzed using the SISVAR statistical program, where analysis of variance (ANOVA) and the Scott & Knott test were performed, both at 5% significance. In this way, the best roughness and surface finish was observed after the 80 – 120 – 220 – 400 grit sanding sequence. In this case, average values of 0.9222 μm and 4.6766 μm were obtained for the Ra and Rz parameters, respectively. Thus, it is concluded that Paricá wood, when properly treated, becomes a viable source for the production of laminated panels due to the low roughness values obtained, a fact that allows greater contact between the wooden sheets, also increasing the adhesion of glues and thus avoiding greater waste.